Morphological Characteristics and Mineral Content Analysis of Magnetic Minerals Based on River and Coastal Sand using SEM-EDX - Lalu A. Didik; Isniwana Damayanti; Jumliati Jumliati; Putri Dinda Alfadia Lestari (Jurnal Sains Dasar, 2021)
This study aims to analyze the mineral content and morphological characteristics of magnetic minerals based on coastal and river sand. Analysis of minerals content uses Atomic Absorption Spectroscopy (AAS) to determine the content of Fe and Energy Dispersive X-Ray (EDX) to determine the elements of magnetic minerals based on coastal and river sand. While the morphological characteristics were analyzed using Scanning Electron Microscope (SEM). Based on the AAS analysis, magnetic mineral based on coastal sand has higher Fe content (9.03 mg/gram) compared to magnetic mineral based on river sand (8.03 mg/gram). This is also confirmed by EDX analysis where the Fe content of magnetic mineral based on coastal sand is 2.07 ± 0.21%. This value is greater than the Fe content of magnetic mineral based on river sand which cannot be measured by EDX. Morphological analysis using SEM shows that magnetic mineral based on coastal sand has a relatively uniform particle size compared to magnetic mineral based on river sand. The particle size of magnetic minerals based on coastal sand also smaller than magnetic minerals based on river sand. Coastal sand also has finer size compared to river sand. This is because coastal sand sediments are formed due to the energy of sea waves so that they have a smoother structure. While river sand sediments come from limestone deposits that have a fine and coarse structure.